2011
DOI: 10.1128/mbio.00180-11
|View full text |Cite
|
Sign up to set email alerts
|

Raw Sewage Harbors Diverse Viral Populations

Abstract: At this time, about 3,000 different viruses are recognized, but metagenomic studies suggest that these viruses are a small fraction of the viruses that exist in nature. We have explored viral diversity by deep sequencing nucleic acids obtained from virion populations enriched from raw sewage. We identified 234 known viruses, including 17 that infect humans. Plant, insect, and algal viruses as well as bacteriophages were also present. These viruses represented 26 taxonomic families and included viruses with sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
250
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 273 publications
(280 citation statements)
references
References 49 publications
26
250
1
Order By: Relevance
“…This nested PCR system, validated on clinical samples, has proved to be a powerful tool for HPV detection even in environmental samples Iaconelli et al, 2015;La Rosa et al, 2015) . Recently, next generation sequencing has been shown to be effective in the detection of a wide range of HPVs, including novel types, in both clinical and environmental samples (Bibby & Peccia, 2013;Bzhalava et al, 2014;Cantalupo et al, 2011;Johansson et al, 2013;Kocjan et al, 2015). Since deep sequencing technologies are continuously evolving with increasing throughput and decreasing costs, it is likely that an expanding diversity of HPVs will continue to be revealed.…”
Section: Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This nested PCR system, validated on clinical samples, has proved to be a powerful tool for HPV detection even in environmental samples Iaconelli et al, 2015;La Rosa et al, 2015) . Recently, next generation sequencing has been shown to be effective in the detection of a wide range of HPVs, including novel types, in both clinical and environmental samples (Bibby & Peccia, 2013;Bzhalava et al, 2014;Cantalupo et al, 2011;Johansson et al, 2013;Kocjan et al, 2015). Since deep sequencing technologies are continuously evolving with increasing throughput and decreasing costs, it is likely that an expanding diversity of HPVs will continue to be revealed.…”
Section: Detection Methodsmentioning
confidence: 99%
“…Table 3 summarizes the studies on HPVs in environmental samples. NR -Not Reported a GC/L= Genome copy number per liter; assuming 1GC =1 viron Cantalupo et al, 2011;Bibby and Peccia, 2013 described observations of HPV 112 and 7, 10, 16, 18, 34, 49, 53, 63, 90, 92, 129 in sewage and sewage sludge in Spain and USA but no quantitative data were available.…”
Section: Data On Occurrence In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent, deep-sequencing analysis of viral metagenomes from sewage and sewage sludge (also known as sewage viromes) has indicated that these novel human picornaviruses can be found in most cases at relatively higher abundance and occurrence than members of the Enterovirus genus (Aw et al, 2014;Bibby and Peccia, 2013;Cantalupo et al, 2011;Ng et al, 2012). Taken together, these studies have demonstrated the importance of targeted molecular assays and unbiased high-throughput sequencing (i.e., metagenomics viral pathogen detection technologies) to the study of virus diversity in waste waters and to monitor shedding of known and newly characterized viral human pathogens on a population level scale.…”
Section: Occurrence In Sewagementioning
confidence: 99%
“…Previous metagenomic studies reveal that wastewater harbors diverse viral species including previously undescribed viruses with unknown viral sequences outnumbering known viral sequences by a factor of 10 to 1,000 [3] . This indicates that raw sewage is an excellent source for previously undescribed viruses.…”
mentioning
confidence: 99%